ANALYSIS OF ACTIVE SCHOOL COMMUTING INFRASTRUCTURE IN OTA, OGUN STATE, NIGERIA - Folasade Jokotade Odekunle; Gabriel Olabisi Adebayo; Hakeem.A Adewole; Ademola James Adedini (Utan Kayu Publishing, 2024)
Active commuting can be enhanced through infrastructure development to promote well-being. Lack of awareness and little or no knowledge of the importance and health benefits reduces the rate at which school children and policymakers value active commuting in Nigeria. The study analysed the activities of active school commuting with cycling in Ota, to provide information on how it would enhance the well-being of young people. Primary (questionnaire) and secondary data were used. A multistage sampling method was adopted. Twenty public schools were identified, and 50% were randomly selected.Â Random sampling was used to select 20 students up to age from each school selected for the survey, therefore having a total of 200 questionnaires. The data were analysed using descriptive statistics and five-point Likert-scales method.Â The findings revealed that the road was not constructed to standard, was not in good condition, and lacked some necessary amenities. Active commuting users were not satisfied with the existing conditions of the road. Well-being indicators revealed that derived active factors have the highest mean score of 4.07, and respected active factors have the lowest mean score of 2.74.Â Active school commuting is a subset of physical activity which promotes wellness and quality of life. It is recommended that the government should rehabilitate the road up to standard and provide necessary amenities for the safety of active commuting users. Local governments also can organize active commuting sports competitions for school children and young ones in their jurisdiction.